2000
DOI: 10.1089/lap.2000.10.71
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Total Extraperitoneal Hernia Repair: Mesh Fixation Is Unnecessary

Abstract: Our experience suggests that mechanically fixing the mesh in the preperitoneal space is unnecessary. Not fixing the mesh avoids possible complications and is not associated with any increased risk of hernia recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 8 publications
6
52
0
4
Order By: Relevance
“…8 We observed post-operative pain at 1 month and at 3 month. We used visual analogue scale for measurement of pain.…”
Section: Discussionmentioning
confidence: 78%
“…8 We observed post-operative pain at 1 month and at 3 month. We used visual analogue scale for measurement of pain.…”
Section: Discussionmentioning
confidence: 78%
“…To date, the series reporting the lowest postoperative chronic pain rates have not used any means of mesh fixation. 34,35,52 Tamme et al 52 and Beattie et al 34 observed 2.55 and 0% chronic pain problems, respectively, after TEP repair, with a recurrence rate of less than 0.6%. However, the largest of these two series did not specify the length of follow-up and the other one was a rather small series (n = 89).…”
Section: Discussionmentioning
confidence: 98%
“…42 Besides nerve damage during dissection, thermal injury due to electrocautery, and inflammatory and/or mechanical reaction to the mesh, stapling of the mesh is the most frequent evocated mechanism. 34,45,48 Among other potential factors causing postoperative pain is the repair of recurrent hernias. There is a great variation in the rate of postoperative chronic pain, ranging from 0.1 to 0.4% and 22.5% 41,45,49 in laparoscopic repairs for which staples are used to attach the mesh.…”
Section: Discussionmentioning
confidence: 99%
“…In both the above mentioned techniques, the hernia sac is reduced, and a large piece of mesh is used to cover the entire inguinal region. Metal staples can be used to hold the mesh in place, however some surgeons believe this is an unnecessary step because it increases costs and also risks due to the possibility of nerve entrapment (31,32). As an alternative to stapling or suturing, the use of fibrin glue can also be explored as a potential option (8,33).…”
Section: Group 4: Laparoscopic Proceduresmentioning
confidence: 99%